Microrna regulation of human choline kinase alpha gene expression and function in cancer cell lines - Pradeep, Raikundalia Sweta (2021)
Choline kinase alpha (CHKA), the first enzyme of Kennedy pathway, has noncatalytic function in tumour onset and progression. Overexpression of chka is a clinical feature in malignant cells and cancerous tissues. microRNAs (miRNAs) are efficient posttranscriptional regulators of gene expression. To date, the regulation of chka gene expression by miRNAs has never been reported. The objective of this work was to exploit the gene regulatory capabilities of chka-targeting miRNAs to downregulate chka expression in breast (MCF7), cervical (HeLa) and liver (HepG2) cancer cells and study the effects of the downregulated CHKA protein levels on cellular processes. miRNAs exhibiting increased potential of interacting with the 3’UTR of chka gene were predicted using online available bioinformatic tools, shortlisted based on predefined selection criteria and the shortlisted miRNA candidates were tested in-vitro to study the miRNA:mRNA interaction in cancer cells. miR-32- 5p, miR-367-3p and miR-876-5p each exhibited strong in silico interaction with chka mRNA, releasing free energy (MFE) lower than -1.00 kcal/mol and fulfilling other predefined criteria for determining strong miRNA:mRNA interactions. Binding of the selected three miRNAs with respective seed sites on 3’UTR of chka mRNA was experimentally validated in MCF7, HeLa and HepG2 cells by luciferase assay. Effects of miRNA:mRNA interaction on chka expression at mRNA and protein levels were examined by qRTPCR and western blot. Cellular functions impacted by miRNA mediated differential chka expression were studied by cell apoptosis assay, cell cycle assay and wound healing assay. Compared to negative control, chka expression levels, in HeLa, HepG2 and MCF7, as a result of transfection with miR-32-5p, miR-367-3p and miR-876-5p were 0.47-fold, 0.62-fold, and 0.76-fold, respectively in MCF7; 0.32- fold, 0.38-fold, and 0.63-fold, respectively in HeLa; 0.44-fold, 0.49-fold and 0.51-fold, respectively in HepG2 indicating maximum reduction was inflicted by miR-32-5p. Similar effect was observed when miR-32-5p was combined with miR-876-5p, which resulted in 0.33-fold chka downregulation in MCF7 cells. Correspondingly, transfection of miR-32-5p also produced the strongest suppression of CHKA protein levels in MCF7 (0.20-fold) and HeLa (0.46-fold) compared to other miRNAs tested. The specificity of miRNA mimics towards chka was verified by the firefly luciferase reporter assay and co-treatment with miRNA specific inhibitors, which led to reversal of the decreased chka levels produced by the miRNAs. The three miRNAss and the pair of miR-32-5p+miR-367-3p each initiated ~50% cells to undergo apoptosis in HeLa and MCF7 cells. Maximum (77% of cell population) cell cycle arrest at the G0/G1 phase was prompted by miR-367-3p in MCF7. Wound repair function plummeted with <50% wound area healed even after 96 hrs in MCF7, HeLa and HepG2 treated with miR-32-5p alone and in combination with miR-367-3p. The data collected in this study showed an inverse relationship between the three miRNA candidates and chka expression level, thus, proving the potential of miR-32-5p, miR-367-3p and miR-876- 5p as biomarkers for early cancer prognosis and anti-cancer remedies in cancer types with over expressed chka as a clinical observation.